Comparing Partial Discharge Inception Voltage for Synthetic Ester and Gas-to-Liquid Insulation Liquids under Lightning Impulse Voltage Using a Transformer Design-Based Test Setup - Müller, Stephan; Braisch, Dieter; Luther, Matthias; Gamil, Ahmed; Schatzl, Franz; Milone, Marco (21st IEEE International Conference on Dielectric Liquids, 2022)
This article describes a test setup and the results of comparing the partial discharge inception voltage of synthetic ester and gas-to-liquid insulation liquids under lightning impulse voltage of positive polarity. The design of the test samples is chosen to simulate a common insulation arrangement of power transformers: a paper-insulated U-shaped copper winding rod vis-`a-vis a copper plane in insulation liquid with a gap between them. Partial discharges are detected via the occurrence of streamers and optical measurement thereof using fluorescent fibre optics, a photomultiplier tube and, an oscilloscope. The results are evaluated by field strength using conversion factors obtained by a finite element method simulation.<br

Comparing Synthetic Ester and Gas-to-Liquid Insulation Liquids Under Lightning Impulse Voltage Using a Creepage Discharge Test Setup - Müller, Stephan; Braisch, Dieter; Luther, Matthias; Gamil, Ahmed; Schatzl, Franz; Milone, Marco (The 7th International Advanced Research Workshop on transformers, 2022)